Influence of initial binary mixture state of matter on heat costs at rectification - M. K. Zakharov; Mohand Abbasi (Тонкие химические технологии, 2014)
Analysis of heat cost for rectification was performed taking into account the phase state of the original mixture. It was proved theoretically that increasing feed vapor fraction leads to decreasing energy consumption in conventional distillation process. With a low excess factor of reflux, total energy consumption by the reboiler and feed heater is greater than for a distillation column without a feed heater. For high excess factor of reflux values the cost of energy consumed by the reboiler can increase even for rising feed vapor fraction. The most economical condition for full condensation of the vapor-liquid feed before entering the distillation column was found